KEPEMIMPINAN VISIONER DALAM ORGANISASI UNTUK MENINGKATKAN BUDAYA MUTU DI SMKN 2 MARABAHAN - Sri Mirnawati; Milawati, Milawati; Hairullah, Hairullah; Aslamiah, Aslamiah; Cinantya, Celia (STKIP Pesisir Selatan, 2025)
Visionary leadership to improve quality culture at SMKN 2 Marabahan can be implemented through various strategies and collaboration with teachers and staff. This research is a qualitative-research with an analysis process using descriptive analysis. Qualitative descriptive data analysis techniques are an approach used to understand, explain, and interpret non-numerical data. Data sources were taken from the principal and one of the teachers through interviews, observations, and documentation. The results of the study indicate that a visionary leader must be able to convey a strategic vision and mission that is inspiring, this can be achieved through regular meetings to improve the teamwork culture between the principal and teachers and be able to integrate technology with educational strategies to create a modern and adaptive learning environment to strengthen the sharing of best practices. The novelty of this study lies in the emphasis on the integration between visionary leadership and quality culture in vocational education environments such as SMKN 2 Marabahan. The focus on vocational education provides a unique perspective considering the need for practical and professional skills in today's job market.